ANALISIS RESPON SISWA TERHADAP PENGGUNAAN VIDEO TIKTOK SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA PADA SISWA SMP - Silva Widya Fitri; Wikanengsih Wikanengsih; Yeni Rostikawati (IKIP Siliwangi, 2022)
Using Tiktok as a medium for teaching Indonesian to seventh-grade junior high school students was the primary goal of this study. Researchers were inspired to conduct this study because to students' growing use of social media, which led them to focus on Tiktok as a platform for learning process activities in this digital age. Additionally, this study aims to find out how students feel about the use of Tiktok as a learning tool for Indonesian. For future learning, the degree of responses and reactions of students to the teaching medium may be used as a guide for future learning. An internet-based distribution of media response surveys was used to gather data for this study, which used a descriptive quantitative research technique The average percentage score for all indicators is then calculated, and the results are matched with the response categories obtained, using the Likert scale (1-5) results. Students from SMPN 1 Batujajar received an average of 85 percent on the overall indicators. Using Tiktok as a medium for studying Indonesian seems to be a success for the learner. However, pupils will be more interested and confident after using media if the presentation of video displays and the structure of information dissemination are given special care.